In vitro propagation of Carica papaya var. PTM-331 from apical meristem - Solis L., Reynaldo (2011)
An in vitro protocol was develop to propagate variety of papaya PTM-331 from apical meristems, with the objective of obtaining vigorous and disease-free seedlings, using tissue culture techniques. Apical buds were obtained from seedlings cultivated in greenhouse and used as explants for meristem dissection. Meristems were cultured on MS basal medium supplemented with 0,5 mg.L-1 of BAP, 0,5 mg.L-1 of AIA and 10 mg.L-1 of adenine for their differentiation. The best multiplication of explants was achieved with the combination of MS medium supplemented with 0,5 mg.L-1 of BAP, 0,5 mg.L-1 of AIA and 0,3 mg.L-1 of AG3, where largest seedlings, with more shoots were obtained. The best medium for rooting was the combination of MS, 3 mg.L-1 of AIB and 5 mg.L-1 of adenine, where 83,33% of rooted plants were obtained.